2024
DOI: 10.3390/ph17010124
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Deep Eutectic Solvents and Its Use to Extract Bioactive Compounds of Pharmaceutical Interest

Cátia Ferreira,
Mafalda Sarraguça

Abstract: The extraction of bioactive compounds of pharmaceutical interest from natural sources has been significantly explored in recent decades. However, the extraction techniques used were not very efficient in terms of time and energy consumption; additionally, the solvents used for the extraction were harmful for the environment. To improve the environmental impact of the extractions and at the same time increase the extraction yields, several new extraction techniques were developed. Among the most used ones are u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 205 publications
0
6
0
Order By: Relevance
“…Thus, another possible explanation might be the different physicochemical properties of solvents, such as polarity, viscosity, pH, etc. [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, another possible explanation might be the different physicochemical properties of solvents, such as polarity, viscosity, pH, etc. [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, another possible explanation might be the different physicochemical properties of solvents, such as polarity, viscosity, pH, etc. [33]. The clear group separation in the score plots (Figures 2A, 3A and 4A) and their distinctly separate clusterization in the corresponding heat maps (Figures 2B, 3B and 4B) indicated that different individual metabolites were more abundant when different solvents and extraction methods were used.…”
Section: Comparison Of the Nades Efficiencies Observed With Vaementioning
confidence: 90%
“…Thus, the aim of the present chapter is to show the advantages of DES use for the extraction of plant proteins and expose some benefits in the purification of these biomolecules, as well as to argue the opportunity areas and challenges to overcome their large-scale application. Ferreira & Sarraguça (2024) report that the selection of the ideal solvent for protein extraction not only has to be focused on obtaining the molecules of interest but also must be a sustainable, biodegradable, and innocuous compound with no negative impact on both the environment and human health. The only solvent that possesses these characteristics is water, however, it cannot be used for all types of extractions, since it does not dissolve hydrophobic compounds due to its high dielectric constant, hence the use of solvents that, at least decrease this environmental impact and are more biodegradable must follow some of the 12 principles of green chemistry (Ferreira & Sarraguça, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Ferreira & Sarraguça (2024) report that the selection of the ideal solvent for protein extraction not only has to be focused on obtaining the molecules of interest but also must be a sustainable, biodegradable, and innocuous compound with no negative impact on both the environment and human health. The only solvent that possesses these characteristics is water, however, it cannot be used for all types of extractions, since it does not dissolve hydrophobic compounds due to its high dielectric constant, hence the use of solvents that, at least decrease this environmental impact and are more biodegradable must follow some of the 12 principles of green chemistry (Ferreira & Sarraguça, 2024). It has been demonstrated that DES are more effective for protein extraction than classical organic solvents and, in addition the extraction efficiency is higher; DES have shown higher selectivity (Molnar et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…A mixture of two or more pure chemicals that, when mixed in the appropriate ratio, results in a eutectic mixture that deviates from ideal thermodynamic behavior is known as a DES. There are strong interactions between the initial components that function as hydrogen bond donors (HBDs), such as citric acid and malic acid, and hydrogen bond acceptors (HBAs), such as choline chloride and betaine [22]. DESs have been proven to have a wide range of applications, including synthesis, extraction, biocatalysis, nanomaterials, biotechnology, electrochemistry, food, cosmetics, drugs, and biofuel [23].…”
Section: Introductionmentioning
confidence: 99%